2019
DOI: 10.1177/1465312519886322
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis on Bolton’s ratios: Normal occlusion and malocclusion

Abstract: Introduction: The purpose of this study was to seek and summarise the Bolton overall index (OI) and anterior index (AI) regarding normal occlusion and Angle’s malocclusion according to gender, and to assess if these indices support Bolton’s standards as general references. Methods: PubMed, LILACS, Embase, CENTRAL and Google Scholar databases were searched up to June 2019 (CRD42018088438). Non-randomised clinical studies, published in English and assessing Bolton’s OI and/or AI in normal occlusion and Angle’s m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 86 publications
(257 reference statements)
2
15
0
Order By: Relevance
“…The Bolton ratios found in this study were within the range reported earlier [ 6 , 7 , 11 , 33 , 34 ]. In comparison to the original Bolton ratios, our sample's anterior Bolton ratio was larger.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The Bolton ratios found in this study were within the range reported earlier [ 6 , 7 , 11 , 33 , 34 ]. In comparison to the original Bolton ratios, our sample's anterior Bolton ratio was larger.…”
Section: Discussionsupporting
confidence: 91%
“…In comparison to the original Bolton ratios, our sample's anterior Bolton ratio was larger. This should be considered when practicing on Iranian patients; still, it should be noted that such results are not definitive, and sometimes, even studies conducted within the same ethnicity and country yield different results [ 6 , 11 ]. The Angle classes were not associated with the anterior and posterior Bolton ratios in this sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are still a conventional part of anthropological research, even though they are more suited for general assessments rather than more or less detailed descriptions of dental morphology. As an example of practical application of odontometry, we can mention measurements conducted on teeth and dental arches as diagnostics in orthodontic treatment planning and post-treatment assessment of the results [6]. Thus, we can see that measurements are widely used for studies in dental research as a method of obtaining objective data for immediate assessments or further calculations.…”
Section: Introductionmentioning
confidence: 99%